Examining the Adoption Intention of Mobile Marketplace Application among Textile Cyber-Entrepreneurs via Technology Acceptance Model - Wan Abdul Ghani, Wan Safra Diyana; Idris, Nur Azimah; Khidzir, Nik Zulkarnaen; Salahudin, Nur Atikah; Ahmed, Shekh Abdullah-Al- Musa (Journal of Advanced Research Design, 2025)
Mobile shopping has become commonplace among customers and retailers worldwide since the evolution in cloud computing and mobile commerce technology. Nonetheless, the adoption of mobile cloud services and applications by entrepreneurs in Malaysia is low and still evolving. It is significant to understand the acceptance of technologies by Malaysian entrepreneurs in particular textile cyber-entrepreneurs for their business sustainability. This study aims to investigate the relevance of Technology Acceptance Model (TAM) in assessing Malaysian textile cyber-entrepreneurs’ tendency to use a mobile marketplace application, which was rarely done previously. TAM assesses users’ perceived usefulness and perceived ease of use in integrating technology into their business, offering insights into their attitudes and behavioural intentions towards the technology. To achieve this, both printed and online questionnaires were distributed according to the name list provided by Perbadanan Usahawan Nasional Berhad (PUNB) where 348 responses were included for thorough statistical analysis. The data were then analysed using Structural Equation Modelling (SEM) – Analysis of Moments Structures (AMOS) 21 in SPSS version 21. The result shows that there are strong positive influences between all the parameters tested, thus concluding the applicability of TAM in measuring the adoption intention of textile cyber-entrepreneurs towards mobile marketplace application utilisation. Future research directions are also suggested in this study.